2020
DOI: 10.3892/or.2020.7588
|View full text |Cite
|
Sign up to set email alerts
|

TIRC7 inhibits Th1�cells by upregulating the expression of CTLA‑4 and STAT3 in mice with acute graft‑versus‑host disease

Abstract: In a previous study, it was demonstrated that T-cell immune response cDNA 7 (TIRC7) levels reflect the efficacy of treatment of patients with acute graft-versus-host disease (GVHD). However, the pathogenesis of TIRC7 in acute GVHD remains poorly understood. Lymphocytes from patients with acute GVHD were selected as targeT cells, and the effects of TIRC7 on cytotoxic T lymphocyte antigen-4 (CTLA-4), T cell activation and cytokine secretion were observed by electroporation. A mouse model of acute GVHD was establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…An investigation has illustrated that STAT3 activation can lead to increased PD‐L1, CTLA‐4 and TIM‐3 expressions and immune response suppression 27,28 . A recent investigation on the role of TIRC7 (T‐cell immune response cDNA7) in STAT3 and CTLA‐4 expressions in T cells has revealed a new STAT3 regulator that confirmed the relationship between STAT3 and CTLA‐4 29 . It has also been shown that despite STAT3, upregulation of immune checkpoint factors could be among the mechanisms that the tumours resist Herceptin treatment 30,31 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…An investigation has illustrated that STAT3 activation can lead to increased PD‐L1, CTLA‐4 and TIM‐3 expressions and immune response suppression 27,28 . A recent investigation on the role of TIRC7 (T‐cell immune response cDNA7) in STAT3 and CTLA‐4 expressions in T cells has revealed a new STAT3 regulator that confirmed the relationship between STAT3 and CTLA‐4 29 . It has also been shown that despite STAT3, upregulation of immune checkpoint factors could be among the mechanisms that the tumours resist Herceptin treatment 30,31 .…”
Section: Discussionmentioning
confidence: 93%
“…27,28 A recent investigation on the role of TIRC7 (T-cell immune response cDNA7) in STAT3 and CTLA-4 expressions in T cells has revealed a new STAT3 regulator that confirmed the relationship between STAT3 and CTLA-4. 29 It has also been shown that despite STAT3, upregulation of immune checkpoint factors could be among the mechanisms that the tumours resist Herceptin treatment. 30,31 To overcome this complication, we combined Herceptin with STAT3 inhibition and observed that STAT3 inhibition along with Herceptin can reduce the expression of the immune checkpoint factors more effectively, leading to a protective response towards cancer cell eradication.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of STAT3 may suppresses Th1 response during tuberculosis infection [ 23 ]. TIRC7 inhibits Th1 cells by upregulating the expression of CTLA‑4 and STAT3 in mice with acute graft‑versus‑host disease [ 24 ]. These results demonstrated that the upregulating of STAT3 may activate NKT cells and suppresses Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…The co-stimulatory and co-inhibitory molecules CTLA-4 and ICOS are involved in the pathogenesis of autoimmune disease ( 36 , 37 ). TIRC7 is involved in regulation of CTLA-4, and its activation leads to increased CTLA-4 expression ( 11 , 38 , 39 ). IR1 cells show higher expression of both CTLA-4 and ICOS than do IR1neg Tregs.…”
Section: Discussionmentioning
confidence: 99%